2009
DOI: 10.3390/medicina45020016
|View full text |Cite
|
Sign up to set email alerts
|

Histology of human glioblastoma transplanted on chicken chorioallantoic membrane

Abstract: Glioblastoma is the most malignant tumor in the range of cerebral astrocytic gliomas. A lot of experimental models are used to evaluate various properties of glioblastoma. Chicken chorioallantoic membrane model is one of them. Objective. To evaluate histology and survival of glioblastoma tumors taken immediately from operating theatre and transplanted on chicken chorioallantoic membrane. Materials and methods. Glioblastoma samples obtained from 10 patients were transplanted onto 200 eggs. Overall, we used 15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In the case of tumour creation from U118, the results are restricted only to one study by Durupt et al (7), where implementation of both cell lines was successful; however, the U87 cell line had a better ability to create noticeable tumours, as previously demonstrated by Balciūniene et al (1). For the U118 line, the intensity of tumour creation was significantly lower; hence, only 40% of inoculated eggs developed a tumour.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the case of tumour creation from U118, the results are restricted only to one study by Durupt et al (7), where implementation of both cell lines was successful; however, the U87 cell line had a better ability to create noticeable tumours, as previously demonstrated by Balciūniene et al (1). For the U118 line, the intensity of tumour creation was significantly lower; hence, only 40% of inoculated eggs developed a tumour.…”
Section: Discussionmentioning
confidence: 95%
“…U87 line cells sticked closely to each other and filled free spaces in a tumour, while U118 cells were loosely arranged. However, the cell density in both cases was much higher than in the normal human brain nerve tissue (1). Furthermore, the histological analysis of tumours revealed the presence of multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the percentage of p53-positive nuclei, which was higher in the tumors grown on the CAM than on rats, did not correlate with the Ki-67 LI. Other researchers have also reported little correlation between this pair of immunohistochemical markers (Cunningham et al, 1997;Balčiũnienė et al, 2009). (x40) Vimentin is an intermediate filament protein, which marks the mesenchymal cell phenotype.…”
Section: U87 Human Glioblastoma Cell Xenografts In Rat Brains and On mentioning
confidence: 99%